NURSING CARE FOR PEDIATRIC GASTROENTERITIS PATIENTS WITH NURSING PROBLEMS OF HYPOVOLEMIA USING HONEY IN THE SRIKANDI ROOM AT THE JOMBANG GENERAL HOSPITAL - Riatus Salamah; Achmad Wahdi; Erna Ts Fitriyah; Faishol Roni; Tiara Fatma Pratiwi (Universitas STRADA Indonesia, 2023)
Background : Gastroenteritis is also a disease characterized by changes in the shape of the stool with excessive bowel movements (more than 3 times in one day) which causes dehydration.Method : This research was conducted with a case study research design. Research data obtained from the results of WOD (interviews, observations, and documents).Result : Inflammation that occurs in the stomach, small intestine, large intestine caused by food infections containing bacteria or viruses, causing symptoms of diarrhea with more frequency with a liquid consistency, while giving ORS with honey can be used as a treatment for diarrhea. Conclusion : Some of the benefits of vitamin C in honey are that it has anti-inflammatory, anti-bacterial, anti-viral and anti-oxidant properties which are useful for dealing with bacteria and viruses that cause diarrhea, giving honey to children with diarrhea.